Thermally and chemically activated biochar obtained in mechanical biological treatment plants for carbon dioxide adsorption - Karimi, Mohsen (2019)
In this study, based on the scopes of CCS strategy and municipal solid waste management, a novel Integrated Environment Management (IEM) strategy has been proposed. In this way, the obtained compost in the mechanical biological treatment from municipal solid wastes has been considered as a source of adsorbents for CO2 capture. In this way, the maturated compost waste was modified by liquid phase treatment with sulfuric acid and thermal treatment at 800 ºC. Then, the prevalent operational conditions of post-combustion processes have been considered to find the best prepared samples for CO2 capture.